Towards a combined estimation of Greenland’s ice sheet mass balance using GRACE and ICESat data - Slobbe, D.C. (author) (2007)
The Greenland ice sheet is sensitive to climate change. Global heating is expected to result in ice mass losses that will contribute to global sea level rise. For this reason monitoring Greenland’s ice mass balance is of utmost importance. Data of both the Ice, Cloud, and land Elevation Satellite (ICESat) laser altimetry mission and the Gravity Recovery and Climate Experiment (GRACE) gravity mission are used to create two independent estimates of Greenland’s ice sheet mass balance over the full measurement period of about 2003 until 2007. For ICESat data, a processing strategy is developed that uses the elevation differences of geometrically overlapping footprints of both crossing and repeated tracks. The dataset is cleaned using quality flags defined by the Geoscience Laser Altimeter System (GLAS) science team. (The GLAS is the sole scientific instrument on ICESat). The cleaned dataset reveals some strong, spatially correlated signals that are shown to be related to physical phenomena like melting glaciers. On the other hand, strong correlation is also visible between the observed elevation differences and the combined effect of roughness and surface slope. Different processing strategies applied to different sets of laser campaigns are used to convert the observed temporal elevation differences to mass changes for 6 different drainage systems, further divided into a region above and below 2000 meter elevation. Here all available laser campaigns are used and outliers are removed using N-sigma thresholding. Both a uniform and non-uniform weighting scheme,used to estimate the elevation changes with respect to a reference epoch, is evaluated. The non-uniform weighting scheme is developed to account for the influence of roughness and surface slope, but it turns out that also signals of interest are sometimes suppressed. In order to obtain our final estimates based on ICESat data, the uniform weighting scheme is applied. For the whole of Greenland the estimated mass change rate is equal to -142.6 Gton/year. This ...